Implementasi Program Pembangunan Rumah Sederhana Sehat pada Kelurahan Parung Serab di Kecamatan Ciledug Kota Tangerang - Annisa Unafti; Rahmat Salam (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
To support the “Tangerang Berbenah” and Government programs through: this program is to accelerate poverty reduction by fulfilling basic rights, reducing the burden of life, and improving the quality of life of underprivileged people by helping people have livable houses. The purpose of this study is to determine the Implementation of the Healthy Simple House Construction Program (PRSS) in Parung Serab Village in Ciledug District, Tangerang City by using indicators of the theoretical policy implementation model from George C. Edward III. The research method used in this study uses a qualitative approach with a descriptive type of research. Data collection are carried out by means of interviews, observations, and documentation. The results of the research in the Communication indicators have been good and effective between the Housing, Settlement land Office, BKM /Urban Village and the community, resource indicators are still inadequate due to insufficient budget resources. The Disposition Indicators have gone well as well as the good attitude shown by the implementers. The bureaucratic structure in the division of responsibilities carried out starting from the Urban Village, BKM Parung Serab Village and Housing, Settlement land Office of The Tangerang City is well carried out, based on clear and systematic SOP.